An illustrated and annotated catalogue of type specimens of Gelechiidae (Lepidoptera) in the Royal Museum for Central Africa (Tervuren, Belgium), with taxonomic changes - Bidzilya, Oleksiy V.; Rajaei, Hossein (Zootaxa, 2024)
Type specimens of 24 species of Gelechiidae described by E. Meyrick and J. Ghesquière deposited in the Royal Museum for Central Africa are discussed. Adult specimens and genitalia of type specimens are illustrated. Genitalia structures are described for most species. The taxonomic position of each species is reviewed, and the following new combinations are proposed: Stomopteryx achyrobathra (Meyrick, 1933), comb. nov., transferred from Aristotelia; Brachmia cirrhopa (Meyrick, 1938), comb. nov., transferred from Proteodoxa; Helcystogramma leucopla (Meyrick, 1938), comb. nov. and Helcystogramma neuroplecta (Meyrick, 1938), comb. nov., transferred from Brachmia; Helcystogramma synclepta (Meyrick, 1938), comb. nov., transferred from Metaplatyntis; Dichomeris craspedotis (Meyrick, 1937), comb. nov., transferred from Trichotaphe; Dichomeris leontovitchi (Ghesquière, 1940), comb. nov., transferred from Cymotricha; Dichomeris pammiges (Ghesquière, 1940), comb. nov., transferred from Gaesa; Dichomeris symbolistis (Meyrick, 1938), comb. nov., transferred from Adoxotricha; Dichomeris opalina (Ghesquière, 1940), comb. nov., transferred from Prasodryas; Dichomeris phaeothina (Ghesquière, 1940), comb. nov., transferred from Trichotaphe; Leuronoma allomima (Meyrick, 1938), comb. nov., transferred from Gelechia; Photodotis modulatrix (Meyrick, 1938), comb. nov., transferred from Aristotelia. Six new synonyms on the generic and the species level are established: Proteodoxa Meyrick, 1938, syn. nov. of Brachmia Hübner, 1825; Metaplatyntis Meyrick, 1938, syn. nov. of Helcystogramma Zeller, 1877; Adoxotricha Meyrick, 1938, syn. nov. of Dichomeris Hübner, 1818; Gelechia ochrocorys Meyrick, 1936, syn. nov. of Armatophallus exoenota (Meyrick, 1918); Phthorimaea tristrigata Meyrick, 1938, syn. nov. of Scrobipalpa ergasima (Meyrick, 1916); Brachmia leucospora Meyrick, 1938, syn. nov. of Scrobipalpa subroseata (Meyrick, 1932). Lectotypes are designated for Proteodoxa cirrhopa Meyrick, 1938 and Epithectis phaeomicta Meyrick, 1936. The latter species is excluded from Epithectis Meyrick, 1895 but no current genus is available. The monotypic genus Paltoloma Ghesquière, 1940 (type species P. paleata Ghesquière, 1940) is removed from the family Gelechiidae, transferred to the family Lecithoceridae and provisionally placed near Notioseus Park, 2018.